REFLEKSI NILAI â€œMOPOâ€™O TANGGALO DUHELOâ€ DI BALIK PENDAPATAN OLEH KUSIR BENDI: STUDI ETNOMETODOLOGI ISLAM - Thalib, Mohamad Anwar (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
Abstract This study aims to reflect on the local cultural values behind the practice of income accounting by bendi drivers. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results of the study found that the way the bendi drivers earn income when they are at the base is through something other than a queuing or lane system. Prospective passengers are free to choose which buggy they want to rent. The income accounting practice is conditional on local cultural values in the form of â€œmopoâ€™o tanggalo duheloâ€ " which means full of patience. The results of this study contribute to the presence of the local culture-based income accounting concept. Keywords : Bendi, Income, Local Culture, Gorontalo, Islamic Ethnomethodology